EU-Korea security cooperation: a new normative partnership? - Chung, Sae Won; Tonra, Ben (Asia Europe Journal, 2023)
The European Union and South Korea have significantly progressed in developing their bilateral relationship since their strategic partnership in 2010. Recently, they have paid considerable attention to strengthening bilateral security cooperation. Against this backdrop, this paper asks three questions: first, what is the current shape of EU-Korea security cooperation; second, how is this cooperation developing and third, what is the future potential of this cooperation. In so doing, the paper revisits bilateral security cooperation with a focus on how shared ideas are the bedrock of the development and progress of bilateral relations. In our study, we identify the European Union and South Korea as having especially strong shared ideas in the areas of non-proliferation, human rights and cybersecurity. As the Union perceives growing strategic importance in the Indo-Pacific Area, it will seek a competent and reliable partner more actively. Therefore, there is tremendous potential for security cooperation especially in an era of escalating geopolitical tension.